The growth and reproduction of the freshwater limpet Burnupia stenochorias (Pulmonata, Ancylidae), and an evaluation of its use as an ecotoxicology indicator in whole effluent testing - Davies-Coleman, H D (Heather D) (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2002)
For the protection of the ecological Reserve in South Africa, the proposed introduction of compulsory toxicity testing in the licensing of effluent discharges necessitates the development of whole effluent toxicity testing. The elucidation of the effects of effluent on the local indigenous populations of organisms is essential before hazard and risk assessment can be undertaken. The limpet Burnupia stenochorias, prevalent in the Eastern Cape of South Africa, was chosen to represent the freshwater molluscs as a potential toxicity indicator. Using potassium dichromate (as a reference toxicant) and a textile whole effluent, the suitability of B. stenochorias was assessed under both acute and chronic toxicity conditions in the laboratory. In support of the toxicity studies, aspects of the biology of B. stenochorias were investigated under both natural and laboratory conditions. Using Principal Component and Discriminant Function Analyses, the relative shell morphometrics of three feral populations of B. stenochorias were found to vary. Length was shown to adequately represent growth of the shell, although the inclusion of width measurements is more statistically preferable. Two of the feral populations, one in impacted water, were studied weekly for 52 weeks to assess natural population dynamics. Based on the Von Bertalanffy Growth Equation, estimates of growth and longevity were made for this species, with growth highly seasonal. Age is not easily discerned from shell size. Egg laying occurred all year round, with early summer (peak egg lay), mid summer (a second, smaller peak in egg lay), and winter (limited presence of eggs) phases. In toxicity testing, consideration is given to the choice of the test organism based on age and sexual development. Consequently, the sexual development of B. stenochorias relative to shell length was determined with the aid of histological examinations of transverse sections of limpets, of all sizes, collected over one year. Limpets less than 3mm shell length were found to be immature in the development of the oocytes and spermatozoa, and were later chosen for acute toxicity tests. A laboratory diet was developed, for both culturing and maintaining of the limpets during toxicity tests; however, the diet requires optimisation. Under laboratory conditions, growth was linear, and individual fecundity highly variable. Successful methods for the collection of limpets from naturally occurring populations, and their acclimation to the laboratory were developed. Three B. stenochorias populations, representing different hydrological and water quality conditions, were compared to a laboratory population (maintained for three years) in their responses to the textile whole effluent and potassium dichromate. Under acute conditions, variability of mortality between limpet populations and between seasons was consistent with acceptable international standards. However, seasonal differences between feral limpets were apparent, with early summer limpets significantly more susceptible to both potassium dichromate and textile effluent than winter limpets. Although mortality occurred within the effluent at all concentrations, no 96 hour LC₅₀ values were obtained. The chronic toxicity effects of the textile whole effluent were assessed over the entire life cycle of B. stenochorias, based on survival, growth and reproductive effects. Lower concentrations of effluent (# 10%) gave greater variability of responses and toxicity than higher concentrations, with a 43 day LC₅₀ of 3.9% effluent. The No Observed Effect Concentrations for survival (over 43 days) were calculated in consecutive years as 0.1% and 1% effluent. Survival is considered a useful tool for determining toxicity endpoints using B. stenochorias. Limpet growth remained linear in effluent, with an apparent stimulation of growth at the 3-10% effluent concentration, confusing the toxicity and variability assessments. The possible addition of nutrients from the effluent points to either a potential inadequacy of the food quality provided in the chronic assessment, or the presence in the effluent of growth stimulants. Growth was also found to be too variable to allow adequate statistical conclusions about the toxicity of the effluent, although it is suggested that growth may be useful in the assessment of single compounds. Despite large individual variability in fecundity, statistical differences were discernible between effluent concentrations. The application of fecundity of B. stenochorias in hazard assessment therefore warrants further investigation. It was concluded that an assessment of textile whole effluent toxicity to B. stenochorias over an entire life cycle, and an F1 generation, is unnecessary. The development of the bucket/plastic bag method for both acute and chronic toxicity assessment of B. stenochorias was useful. In the final assessment of the usefulness of B. stenochorias as a toxicity indicator, toxicity endpoints were compared with those of the standard laboratory organism Daphnia pulex. Both in acute and chronic toxicity, B. stenochorias was found to be more sensitive. B. stenochorias is therefore considered valuable as a South African freshwater molluscan ecotoxicological indicator, with a place in hazard assessment, although further development and research is necessary before the limpet can be effectively used.
Keywords: Ancylidae; Effluent quality; Toxicity testing